"Jag skulle gärna vilja, men jag gör inte det..." - En kvalitativ studie om handlingsutrymme i implementeringen av MI - Numminen,Sanna (2014)
The aim of this study was to examine how implementation of MI affects the social workers discretion based on the requirements of evidence-based practice and on consideration of user perspective. The study was conducted with seven semi-structured interviews. A theoretical framework including Max Weber´s Ideal types of social action and Michael Lipsky´s Street-level bureaucracy has been used to analyze the results. Study results show that MI can provide an individual use depending on the interpretation of MI and the discretion that is created in the practitioners own work. MI was used with an emphasis on user participation and fair treatment. Evidence was considered important, but the requirement to keep up-to-date on research of MI according to evidence-based practice was made little based on importance to cooperation and advice amongst colleagues.
Keywords: MI; Motivational Interviewing; social services; implementation; discretion